ANALISIS PENGGGUNAAN LITERASI DIGITAL BERBASIS MEDIA PEMBELAJARAN INFORMATIKA DI SMK ASKHABUL KAHFI SEMARANG - Ainul Hayya Maulana, Vicky; Wijaya, Imron (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
Digital literacy is one type of literacy that must be mastered by Indonesian citizens. Strengthening digital literacy is inseparable from fostering a culture of literacy. The implementation of digital literacy in schools is a must in the form of informatics learning media. Information technology (informatics) subjects in schools are one of the compulsory subjects. Analysis of the application of digital technology-based informatics learning media in schools is needed. This study aims to determine and analyze ICT learning facilities in schools and the extent to which the utilization of informatics learning media is implemented at SMK Askhabul Kahfi Semarang in supporting digital literacy. Using qualitative research methods and analyzed with the Creswell model. The results showed that the informatics learning media used made students learn happily and helped educators. The impact is expected to be that students understand digital literacy as a whole so that students get benefits.